Changes in empowerment and anxiety of patients and parents during genetic counselling for epilepsy. (May 2021) - Vlaskamp, Danique R.M.; Rump, Patrick; Callenbach, Petra M.C.; Brilstra, Eva H.; Velthuizen, Mary E.; Brouwer, Oebele F.; Ranchor, Adelita V.; van Ravenswaaij-Arts, Conny M.A.
Abstract: Genetic testing and counselling are increasingly important in epilepsy care, aiming at finding a diagnosis, understanding aetiology and improving treatment and outcome. The psychological impact of genetic counselling from patients' or parents' perspectives is, however, unknown. We studied the counselee-reported outcome of genetic counselling before and after genetic testing for epilepsy by evaluating empowerment – a key outcome goal of counselling reflecting cognitive, decisional and behavioural control, emotional regulation and hope – and anxiety. We asked patients or their parents (for those <16 years or intellectually disabled) referred for genetic testing for epilepsy in two university hospitals between June 2014 and 2017 to complete the same two questionnaires at three timepoints: before and after pre-test counselling and after post-test counselling. Empowerment was measured with the Genetic Counselling Outcome Scale (GCOS-18); anxiety with the short State Trait Anxiety Inventory (STAI-6). A total of 63 participants (55 parents with the age of 29–66 years; 8 patients with the age of 21–42 years) were included in our study. Empowerment significantly increased during the genetic counselling trajectory with a medium effect size ( p < 0.001, d = 0.57). A small but significant increase in empowerment was already seen after pre-test counselling ( p = 0.038, d = 0.29). Anxiety did not change significantly during the counselling trajectory ( p = 0.223, d = −0.24). Our study highlights that patients with epilepsy or their parents show a clinically relevant increase in empowerment after genetic counselling. Empowerment was already increased after pre-test counselling, suggesting the importance of counselling before initiating genetic testing for epilepsy. However, individual differences in changes in empowerment and anxiety were seen, suggesting that counselling could be further improved, based on individual needs. Highlights: Genetic testing and counselling are increasingly essential in epilepsy care. Our study gives insight in outcomes of genetic counselling for epilepsy. Counselees for epilepsy show an increase in empowerment after genetic counselling. Counselling sessions can be further improved based on individual needs.